2011
DOI: 10.3844/ajeassp.2011.42.51
|View full text |Cite
|
Sign up to set email alerts
|

Freezing and Thawing Durability of Very High Strength Concrete

Abstract: Problem statement: The newly developed Very High Strength Concrete (VHSC), having compressive strengths of 29 ksi and flexural strengths of 6 ksi, represents a breakthrough in concrete technology. Study to further enhance the properties of this new concrete is continuing. Approach: The objective of this study is to investigate the effect of exposing Very High Strength Concrete (VHSC) specimens to rapid freeze/thaw cycles. Twenty one specimens were tested according to the Stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Concrete's freeze-thaw resistance depends of the resistance of each component to freezing and thawing [11]. The typical UHPC mixture consists of: sand, cement, microsilica, crushed quartz sand, fibers, superplasticizer and water.…”
Section: Introductionmentioning
confidence: 99%
“…Concrete's freeze-thaw resistance depends of the resistance of each component to freezing and thawing [11]. The typical UHPC mixture consists of: sand, cement, microsilica, crushed quartz sand, fibers, superplasticizer and water.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, since mixture and molding of the concretes become difficult upon use of fiber content over 1 %, they contain gaps more according to other fiber ratios and consequently the free water in gaps freezes and its volume increases in the freeze-thaw cycles, gaps in the concrete increase and cause absorption of more water. 48 In the concrete series containing SEPRC, it is observed that there is a smaller increase than the others with respect to water absorption in the inspection and 0.5 % fiber contents.…”
Section: Freezing-thawing Testmentioning
confidence: 99%
“…Many scientists agree with idea that pozzolanic materials (silica fume, fly ash, metakaolin, blast furnace slag) can improve structure of concrete and decrease permeability to moisture of cement matrix and interfacial transition zone. [15][16][17]. T.P.…”
Section: Introductionmentioning
confidence: 99%